HEPATITIS C IN RURAL AREAS OF ISLAMABAD, PAKISTAN - Saleem, K.; Qureshi, T. Z. (The Nucleus, 2010)
Hepatitis is recognized as significant public health problem worldwide. There are one hundred and seventy five million Hepatitis C virus carriers around the world. Global prevalence ranges from 0.1 to 5 % with an average of 3 %. There are very few studies done at national and international levels to find the prevalence of HCV in our population. It is a Picorna virus that may invade the body usually through, intra venous devices and contaminated instruments. It may remain silent for years or cause acute hepatitis to chronic liver disease. Hepatocellular carcinoma is well known complication. Most of the epidemiological studies have so far been carried out on the population with high socioeconomic status attending tertiary care hospitals in the cities that have good sterilization techniques. Whereas rural dispensaries are the drainage zones for HCV due to unqualified and untrained technical staff and lack of sterilization procedures. We, therefore, selected some villages (Chirah, Tumair, Thanda pani and Alipur) around Islamabad to assess the prevalence of HCV and tried to compare different epidemiological factors with urban areas in this randomized cross-sectional study conducted from May to August 2009. Two hundred asymptomatic volunteers were randomly selected from patients attending local dispensaries in this study zone. The subjects were given a detailed questionnaire to study and fill accordingly. Details of study were explained to them. Patients included in the study were between 20-50 years of age, having gastrointestinal symptoms. Excluded subjects were pregnant women, patients on ant-viral therapy and known cases of HCV. 5 cc blood samples were taken and transported in ice containers to PINSTECH Complex Hospital laboratory within two hours for chromatographic analysis. We observed that 16.5% of the individuals were infected with HCV. Invasive procedures like D&C by dais and ear piercing were the major transmitting factors in females, whereas I/V devices, dental treatments and barber cutting in males was the dominant risk factors. The use of non disposable glass syringes for injection was also an important mode of transmission.